METHODICAL ASPECTS OF CREATING AND USING THE LANGUAGE EBOOKS IN PRIMARY SCHOOL - Khyzhnyak І.А. (Journal of Information Technologies in Education (ITE), 2016)
In the article the important role of electronic linguomethodical tools use in primary school and one of the largest groups of this means – Ukrainian language e-books are substantiated. This group contains, in author opinion, the different types of tools: visual (multimedia presentations,infographics, interactive posters, etc.), practical (learning language games, training language aids,interactive crosswords, etc.); studying (learning language aids, etc). Each type has its creating and using methodical features in primary school. In addition, the use of various kinds of e-books must be systematic and take linguomethodical patterns of language teaching in primary school.The author gives a brief description each type of language e-books for primary school, describes the methods of their application and gives general guidance on their implementation in the learning process. A teacher is able to design and make all these types of electronic training manuals in Ukrainian language on his own using free software that allows to take into account the typical class features, its gender specificity, primary schoolchildren’s interests, to process local country studying information. In the conclusion author gives the main requirements to Ukrainian language e-books for a primary school: available and interesting for each pupil, despite the level of language development, use multimedia and hyperlinks, interactivity, predictable methodology of working with electronic trainers should be maximum simple, and its design should have national-patriotic character etc.